A new heterofunctional amino-vinyl sulfone support to immobilize enzymes: Application to the stabilization of β-galactosidase from Aspergillus oryzae. (January 2018) - Zaak, Hadjer; Sassi, Mohamed; Fernandez-Lafuente, Roberto
Graphical abstract: Highlights: A new heterofunctional support (amino.-vinylsulfone) has been designed. The β-galactosidase from A. oryzae could not be immobilized on vinylsulfone supports. The enzyme becomes rapidly immobilized on the new heterofunctional support. Immobilized properties depended on the immobilization pH, incubation and time of incubation and blocking reagent. Abstract: The paper shows the preparation of a new heterofunctional agarose support: amino-vinylsulfone. This has been employed to immobilize the interesting enzyme β-galactosidase from Aspergillus oryzae . The enzyme cannot be immobilized on just vinylsulfone activated support a pH values ranging from 5.0 to 9.0. Neither the enzyme was immobilized using 200 mM of NaCl on amino-vinylsulfone support. However, the enzyme was readily immobilized at moderate ion strength at pH values from 5.0 to 9.0 via ion exchange on amino-vinylsulfone support, and later some covalent enzyme-support bonds could be formed, more rapidly at alkaline pH value. After optimization of immobilization pH, incubation pH and time, and blocking reagent, several immobilized biocatalysts on amino-vinylsulfone support having 50–80% of the initial activity and a stabilization factor of around 8–15 were prepared, depending on the exact immobilization conditions.